ATRIAL SEPTUM FENESTRATION FOR PATIENT WITH IDIOPATHIC PULMONARY ARTERY HYPERTENSION - V. V. Plechev; T. Z. Aminov; I. V. Buzaev; I. E. Nikolaeva; B. A. Oleynik; G. A. Khalikova; A. I. Davletbaeva (Креативная хирургия и онкология, 2018)
Introduction. Pulmonary arterial hypertension (PAH) is a rare disease of unknown etiology, characterized by increased resistance of pulmonary vessels, which leads to right ventriculae heart failure and, eventually, death. At the same time, according to the literature, it has been established that the presence of an atrial septum defect in patients with idiopathic PAH (iPAH), is accompanied by a longer life expectancy, improves its quality and is the prevention of sudden death due to the development of a pulmonary hypertensive crisis. We decided to perform an operation to create an atrial septum communication (ASC) in patients with iPAH.Materials and methods. Clinical cases showed efficiency in creating interatrial septum fenestration by implantation of intentionally fenestrated occluder in patients with PAH.Results. It was in studies revealing that the advantage of this method as compared to others is close good fixation of the device on interatrial baffle which reduces possibility for the device to migrate from fixed position in the heart cavity and to reduce intra-operative complication. After implantation of fenestrated occluder the patients showed significant improvement of life quality: decrement of breathlessness, higher tolerance to physical exertion, less swelling in lower limbs, absence of syncopal condition. Such procedure perhaps prolongs life time.Conclusion. Implantation of fenestrated occluder, modified in intra-operative conditions, can be an adequate method to help patients with iPAH, under conditions of unavailability of special devices in the market.